Development and Evaluation of a Laminated Bamboo Frame for Electric Scooters: A Preliminary Prototype - Safarudin Gazali Herawan; Ismail Azizi Martalogawa; Azqy Nur Farenzy Saputra; Ahmad Hanif Moenartioso; Ihwan Ghazali (Engineering Science Letter, 2025)
This study presents the design, fabrication, and evaluation of a hybrid electric scooter frame constructed from laminated Gombong bamboo and aluminium. The objective was to address environmental concerns in personal mobility by reducing reliance on high-carbon materials and improving battery safety. A CAD-based design was executed in Autodesk Inventor using bamboo beams for primary structure and aluminium joints for mechanical stability. Laminated bamboo was processed through drying, chemical treatment, and gluing. Mechanical properties were evaluated via tensile and compressive tests, achieving a tensile strength of 289 MPa. A 72V lithium-ion battery pack composed of 18650 cells was assembled with BMS integration. The resulting prototype exhibited a total frame weight of 4.8 kg and a 30 km range per charge. The integration of laminated bamboo with aluminum joints provides preliminary evidence of feasibility and highlights bamboo’s potential as a renewable material for lightweight mobility applications. These results provide an initial prototype-level demonstration of laminated bamboo as a viable material for sustainable transport applications.